Synergistic upconversion and molecular imprinting in flame-made Yb/Nd co-doped TiO2 for targeted photocatalytic degradation of tetracycline in complex water - Xinhao Meng; Shuohan Wu; Zhijun Yang; Heran Zhang; Zhengliang Bian; Dongliang Zhang; Shuning Xiao; Yanjie Hu; Ying Li; Wei Bi (Environmental Research, 2026)

Bridging zero-dimensional loss units with one-dimensional carbon nanotubes for gradient-laminated polyarylene ether nitrile composites toward absorption-enhanced electromagnetic interference shielding - Jiabin Hu; Yunfeng Guo; Yu Zheng; Ting Zhang; Shaoqian Zhou; Yani Chen; Mei Liu; Qian Xiao; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Self-generated microporous hydrogel coating on mesoporous silica: A hierarchical porous structure for high-performance HILIC - Shuning Li; Tong Zhang; Xiaojing Liang; Lei Wang; Yong Guo (Analytica Chimica Acta, 2026)

Microdomain contraction and crystalline refinement in polyarylether nitrile alloys for high-temperature dielectric stability - Ting Zhang; Hongbo Shen; Youbin Wan; Yani Chen; Qian Xiao; Shaoqian Zhou; Yunfeng Guo; Jiabin Hu; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Contribution of dihydroorotate dehydrogenase complex to NADH supply and metabolic flux redirection in Clostridium acetobutylicum - Dandan Jiang; Jihong Yi; Haifeng Zhu; Liangliang Gao; Shuning Wang; Guodong Liu; Lanpeng Li; Quan Zhang; Meng Wang; Armin Ehrenheich; Fuli Li; Yihua Xiao; et al. (Bioresource Technology, 2026)

Voronoi curvature scaffolds rejuvenate senescent stem cells and enhance aged bone regeneration - ZuFu Lu; Renugaa Suresh Babu; Iman Rhohani; Rana Judeh; Shuning Wang; Yiran Zhang; Yufan Zhu; Vimalraj Selvaraj; Swathi Sudhakar; Hala Zreiqat (Chemical Engineering Journal, 2026)

Analysis of Rockfall Motion Characteristics Based on a 3D DDA Stochastic Model: A Case Study of the Houyu Tunnel in Fujian Province - Lu Zheng; Zhiyuan Zhu; Yihan Wu; Shuning Zhang; Zhiyuan Li; Zishuang Han; Manchao He; Guangqi Chen (Rock Mechanics and Rock Engineering, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Functional identity of typhoon-derived green litter overrides functional dissimilarity in reshaping litter faunal feeding guilds in a subtropical forest - Shuning Ma; Lifeng Wang; Qingjun Ma; Ajuan Zhang; Rui Cao; Zhuang Wang; Qin Wang; Mei Qin; Wanqin Yang (Plant and Soil, 2026)

Tailoring the surface acidity and electronic structure of (Ce, La)PO4 via Fe modification for low-temperature NH3-SCR - Na Li; Yalin Huang; Xin Jin; Shuning Tan; Ruifang Wang; Zhiyu Zhang (Journal of Environmental Chemical Engineering, 2026)

Janus structured magnetic MOFs-polyarylether nitrile/MXene composite films with gradient interfaces for electromagnetic interference shielding and thermal management - Yunfeng Guo; Jiabin Hu; Xin Sun; Ting Zhang; Shaoqian Zhou; Liang He; Hongbo Shen; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Coarse Woody Debris Maintains Two Distinct and Interrelated Detrital Food Webs in Forest Ecosystems - Zhihui Wang; Yuchen Lu; Shuning Ma; Benjuan Liu; Rui Cao; Lifeng Wang; Yong Zhang; Wanqin Yang (Ecosystems, 2026)

Characteristics of overburden failure and evolution of the water-conducting fracture zone in downward mining of close distance coal seams: a case study of the Shaozhai Coal Mine - Bo Liu; Shuning Dong; Xiaoming Guo; Xinqing Wu; Gang Zheng; Xingling Dong; Lei Liu; Xiyu Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Classification and Evaluation of a Shale Oil Reservoir in the Qingshankou Formation in the Southern Songliao Basin, NE China - Guofeng Wang; Dawei Zhang; Liang Yang; Yongqing Zhang; Junling He; Jilin Xing; Jun Jiang; Jijun Li; Shuning Zhang; Chenxu Yan; Hang You; Ketao Zheng; et al. (Journal of Earth Science, 2026)

The Training Effect of Tactical Awareness and Technical-Tactical Performance Among Youth Football Players: A Systematic Reviews and Meta-analysis - Jiahui Hu; Yeqin Zhang; Shuning Liu; Danyang Li; Dingmeng Ren (Journal of Science in Sport and Exercise, 2026)

The Effect of Mining Activities on the Hydrochemical and Isotopic Characteristic of Groundwater in the Shennan Coal Mine, Shaanxi Province, Northwest China - Ankun Luo; Shuning Dong; Hao Wang; Shouchuan Zhang; Haidong Cao; Shidong Wang; Zhongkui Ji; Xiaoyu Hu (Mine Water and the Environment, 2026)

Oil-in-water emulsions stabilized by hollow particles of zein and whey protein: Particle integrity, interfacial structure and interfacial adsorption - Kaiwen Chen; Qianqian Shen; Bohua Zhang; Shuning Zhang; Qi Fan; Gong Chen; Li Liang (Food Hydrocolloids, 2026)

Contrasting photochemical behaviors between biogenic-sourced and combustion-sourced dissolved organic nitrogen - Zhiyuan Zhang; Xiurui Cui; Chenhui Wei; Shuning Zang; Shu Tao; Dongqiang Zhu (Geochimica et Cosmochimica Acta, 2025)

Evolution of phenylalanine ammonia-lyase protein family from algae to angiosperm - Chao Zhang; Huan Guo; Zhongling Li; Shuning Yue (Functional & Integrative Genomics, 2025)

Differential profiles of antibiotic resistance genes in activated sludge and biofilm in wastewater treatment plants - Haohao Sun; Weiyao Li; Shuning Zhang; Lingjue Yuan; Di Wang; Jiayue Sun; Hongyu Wang (Journal of Hazardous Materials, 2025)

Combining machine learning and multi-objective optimization algorithms to optimize key parameters for underground hydrogen storage - Zhengyang Du; Zhenxue Dai; Shangxian Yin; Shuning Dong; Xiaoying Zhang; Huichao Yin; Mohamad Reza Soltanian (Gas Science and Engineering, 2025)

Matrix crystallinity and nanofiller compatibility optimization of polyarylether nitrile nanocomposite films for enhanced high-temperature energy storage - Ting Zhang; Yani Chen; Shaoqian Zhou; Jinqi Wu; Yunfeng Guo; Jiabin Hu; Qian Xiao; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2025)

Crop rotation and organic fertilizer maintains diversity and activity of cbbL-carrying CO2-fixing bacteria in reclaimed coal mining soils - Shuning Bai; Meihua Fan; Min Wu; Xiaolong Sui; Yibo Song; Yunlong Jiang; Huisheng Meng; Yulin Liu; Xiangying Wang; Xianjun Hao; Yi Li; Jianping Hong; et al. (European Journal of Soil Biology, 2025)

Covalent interface and crosslinked network engineering enable polyarylene ether nitrile nanocomposites with enhanced thermal conductivity and high-temperature energy storage - Shuning Liu; Yani Chen; Jinqi Wu; Ting Zhang; Lifen Tong; Xiaobo Liu (Chemical Engineering Journal, 2025)

Interfacial optimization design and thermal conduction mechanism study of polyarylene ether nitrile composites based on condensed state structure regulation - Lifen Tong; Jinghui Zhang; Liang He; Xiaobo Liu; Shuning Liu (Chemical Engineering Journal, 2025)

Initiation mechanism of split grouting cracks at the top of the Ordovician limestone in a coal seam floor - Liu Zhaoxing; Dong Shuning; Zhang Qi; Sun Qiang (Carbonates and Evaporites, 2025)

Keystone ecological cluster rather than the whole community of phoD-encoding bacteria driving ecological function and the improvement of yield under long-term organic regime in greenhouse - Xiaoxia Li; Pengjie Li; Muhammad Awais; Zhu Zhang; Shuning Zhao; Yufeng Liu; Zhouping Sun; Hongdan Fu; Tianlai Li (Agriculture, Ecosystems & Environment, 2025)

Enhanced low-temperature waste heat recovery in ethyl acetate / cyclohexane separation using heat integration and ORC - assisted pressure - swing distillation - Yanchao Xue; Qingrui Zhang; Shuning Jiang; Cai Wang; Qian Lin (Process Safety and Environmental Protection, 2025)

Development of a Colloidal Gold Immunochromatographic Strip for Specific Detection of Photobacterium damselae subsp. piscicida - Shuning Zhang; Jianbai Zhang; Yan Gao; Dandan Zhou; Binzhe Zhang; Xuepeng Li; Jian Zhang (Journal of Fish Diseases, 2025)
Photobacterium damselae subsp. piscicida (Pdp) is characterised by high infectivity and mortality and wide distribution, resulting in substantial economic losses to the global aquaculture industry. Therefore, it is critical to develop a simple, rapid and accurate diagnostic method for Pdp detection. Herein, two Pdp‐specific monoclonal antibodies (mAbs 1H7 and 6E6) were obtained, indirect enzyme‐linked immunosorbent assay and immunofluorescence analysis confirmed that the mAbs specifically recognised the outer membrane of Pdp but could not recognise the other Gram‐positive or Gram‐negative bacteria, indicating good specificity. A colloidal gold immunochromatographic strip (CGICS) was developed here for Pdp detection by optimising the colloidal gold labeling and antibody coating conditions using 1H7 as a colloidal gold‐labelled antibody and 6E6 as a coated antibody. The CGICS exhibited a detection limit of 1 × 10 5 CFU/mL for Pdp and a detection time of 10 min. Cross‐reaction analysis revealed that the CGICS could specifically detect different Pdp isolates without cross‐reaction with the other bacterial species or the subspecies P. damselae subsp . damselae . Stability analysis revealed that the CGICS were stored in closed plastic packaging at 25°C and 4°C for more than 8 months. The CGICS retained their detection limit after 6 months at 4°C, and 4 months at 25°C. Using tissues from the experimentally challenged Lateolabrax maculatus , the CGICS and polymerase chain reaction revealed a 100% coincidence rate. These findings indicated that the established CGICS exhibits high specificity and sensitivity. It is rapid and simple for Pdp detection, making it a potential on‐site tool for Pdp detection in fish aquaculture.

Cytological and metabolomic analysis of Citrus fruit to elucidate puffing disorder - Ting Wang; Shuqi Zheng; Fuzhi Ke; Shiyi Zhang; Jinping Xiao; Xuepeng Sun; Shuning Zhang; Lanlan Zhang; Jinli Gong (Food Chemistry, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Aerobic granular sludge inoculant for enhancing high salinity wastewater treatment: Performance and value-added biopolymer recovery - Haifeng Zhang; Shuning Wang; Sudan Lin; Yuanyuan Miao; Dong-Hoon Kim; Boyan Xu; Wenfeng Du; Xueqing Shi; Shujuan Huang (Chemical Engineering Journal, 2024)

Synthesis of ultrafine Mo2N particles supported on N doped carbon material for guaiacol hydrodeoxygenation - Chenglong Wen; Shuning Li; Peng Zhang; Mohong Lu; Jie Zhu; Mingshi Li; Chunshan Song (Biomass and Bioenergy, 2024)

Functional Characterization of Chinese Cabbage BrCML49 Gene in Pollen Germination and Pollen Tube Elongation and the Regulation of Ca2+-Mediated Self-Incompatibility Response - Chunshu Lyu; Mengting Mao; Jianyu Huo; Shuning Cui; Lugang Zhang; Shanshan Nie (Journal of Plant Biology, 2024)

Micro-transcriptome analysis reveals miRNA-mediated survival strategies between megalocytivirus RBIV-C1 and Scophthalmus maximus - Jian Zhang; Xiangyi Sun; Shuning Zhang; Xuepeng Li (Aquaculture, 2024)

Utilization of γ-polyglutamic acid/pectin hydrogel with 1-MCP on the apricot storage - Shuning Yang; Jinfeng Zhang; Xiaopei Hu; Suhong Li; Tuoping Li (Journal of Stored Products Research, 2024)

Impact of long-term mining activity on groundwater dynamics in a mining district in Xinjiang coal Mine Base, Northwest China: insight from geochemical fingerprint and machine learning - Ankun Luo; Shuning Dong; Hao Wang; Zhongkui Ji; Tiantian Wang; Xiaoyu Hu; Chenyu Wang; Shen Qu; Shouchuan Zhang (Environmental Science and Pollution Research, 2024)

The synergistic nucleation of iodous acid and sulfuric acid: A vital mechanism in polluted marine regions - Haotian Zu; Shaobing Zhang; Shuning Li; Ling Liu; Xiuhui Zhang (Atmospheric Environment, 2024)

Insights into Mn loaded carbon-silica-membrane based catalytic ozonation process for efficient wastewater treatment: Performance and mechanism - Shuning Chen; Tengfei Ren; Zuoyong Zhou; Kechao Lu; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

Mn-doped carbon-Al2SiO5 fibers enable catalytic ozonation for wastewater treatment: Interface modulation and mass transfer enhancement - Tengfei Ren; Changpei Ouyang; Zuoyong Zhou; Shuning Chen; Mengxi Yin; Xia Huang; Xiaoyuan Zhang (Journal of Hazardous Materials, 2023)

Robust adaptive control for dynamic positioning vehicles in presence of adjustable threshold rule and input constraints - Guoqing Zhang; Shuning Lv; Chenfeng Huang; Xianku Zhang (Ocean Engineering, 2023)

MnNx-Carbon-Silica-Framework for highly efficient heterogeneous catalytic ozonation of electron-rich organics through nonradical pathway - Shuning Chen; Tengfei Ren; Kechao Lu; Changpei Ouyang; Xia Huang; Xiaoyuan Zhang (Chemical Engineering Journal, 2023)

Electrospun nanofibres containing Zn-MOF for electrochemiluminescent determination of fenpropathrin residues in fruit juices - Zhuo Sun; Juan Lu; Xin Zhang; Xiangyu Shan; Qian Wu; Chao Li; Huiling Li; Shuning Yang; Li Tian (Food Chemistry, 2023)

Unexpectedly significant stabilizing mechanism of iodous acid on iodic acid nucleation under different atmospheric conditions - Ling Liu; Shuning Li; Haotian Zu; Xiuhui Zhang (Science of The Total Environment, 2023)

Efficient catalytic ozonation via Mn-loaded C-SiO2 Framework for advanced wastewater treatment: Reactive oxygen species evolution and catalytic mechanism - Shuning Chen; Tengfei Ren; Xiaoying Zhang; Zuoyong Zhou; Xia Huang; Xiaoyuan Zhang (Science of The Total Environment, 2023)

Comparative transcriptome analysis reveals the immune response of turbot (Scophthalmus maximus) induced by inactivated bivalent vaccine - Jian Zhang; Shuning Zhang; Xiangyi Sun; Xiudan Xu (Fish & Shellfish Immunology, 2023)

Directed evolution of the PobR allosteric transcription factor to generate a biosensor for 4-hydroxymandelic acid - YaoYao Liang; Juan Luo; Chenhao Yang; Shuning Guo; Bowen Zhang; Fengqianrui Chen; Kairui Su; Yulong Zhang; Yi Dong; Zhihao Wang; Hongda Fu; Guangchao Sui; et al. (World Journal of Microbiology and Biotechnology, 2022)

Discussion on Some Topical Issues of Water Prevention and Control in Coal Mines - Shuning Dong; Wenzhong Zhang; Wanfang Zhou; Rui Chai; Hao Wang; Chunhu Zhao; Xingling Dong; Qiangmin Wang (Mine Water and the Environment, 2021)

Experimental study on freezing and thawing deformation of geogrid-reinforced silty clay structure - Rongfei Zhao; Shuning Zhang; Jin He; Wei Gao; Dan Jin; Liqun Xie (Bulletin of Engineering Geology and the Environment, 2020)

Saponins as modulators of nuclear receptors - Tiehua Zhang; Shuning Zhong; Tiezhu Li; Jie Zhang (Critical Reviews in Food Science and Nutrition, 2020)

Factors effecting the freeze thaw process in soils and reduction in damage due to frosting with reinforcement: a review - Rongfei Zhao; Shuning Zhang; Wei Gao; Jin He; Jie Wang; Dan Jin; Bo Nan (Bulletin of Engineering Geology and the Environment, 2019)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

Estrogenicity of halogenated bisphenol A: in vitro and in silico investigations - Jie Zhang; Tiezhu Li; Tuoyi Wang; Cuiping Yuan; Shuning Zhong; Tianzhu Guan; Zhuolin Li; Yongzhi Wang; Hansong Yu; Quan Luo; Yongjun Wang; Tiehua Zhang (Archives of Toxicology, 2018)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)

The Master Quorum-Sensing Regulator OpaR is Activated Indirectly by H-NS in Vibrio parahaemolyticus - Yiquan Zhang; Lingyu Zhang; Shuning Hou; Xinxiang Huang; Fengjun Sun; He Gao (Current Microbiology, 2016)

Radiation-Induced Bystander Effects in A549 Cells Exposed to 6 MV X-rays - Shuning Yang; Jing Xu; Weixian Shao; Chong Geng; Jia Li; Feng Guo; Hui Miao; Wenbin Shen; Tao Ye; Yazhou Liu; Haiting Xu; Xuguang Zhang (Cell Biochemistry and Biophysics, 2015)

Instability in mitochondrial membranes in Polima cytoplasmic male sterility of Brassica rapa ssp. chinensis - Ying Li; Tongkun Liu; Weike Duan; Xiaoming Song; Gongjun Shi; Jingyi Zhang; Xiaohui Deng; Shuning Zhang; Xilin Hou (Functional & Integrative Genomics, 2014)

A cDNA Clone of BcHSP81-4 from the Sterility Line (Pol CMS) of Non-heading Chinese Cabbage (Brassica campestris ssp. chinensis) - Tongkun Liu; Xilin Hou; Jingyi Zhang; Yuping Song; Shuning Zhang; Ying Li (Plant Molecular Biology Reporter, 2011)